Relacionamento amoroso: experiências afetivo-sexuais dos jovens na atualidade - Nogueira, Natália Souza [UNESP]; Zocca, Adriana Rodrigues [UNESP]; Muzzeti, Luci Regina [UNESP]; Ribeiro, Paulo Rennes Marçal [UNESP] (My University, 2014)
Love experiences have changed along time and have set new meanings, especially for young people. Thus, this qualitative research aimed at understanding the meanings of love relationships, hooking up and dating in the vision of ten adolescents between 17 and 23 years old using a questionnaire. The results revealed that the hooking up is permeated by kisses, fondling and even by sexual intercourse in a short period of time and often through the intermediary of a friend at the time of the conquest. The commitment of dating, on the other hand, is established when love is present in the relationship. Therefore, adolescents revealed that opt for dating, which can begin in the hooking up. However, in the opinion of the participants, the young people's preference nowadays is the hooking up.

As vivências amorosas se transformaram ao longo do tempo e estabeleceram novos significados, em especial para os jovens. Sendo assim, esta pesquisa, de caráter qualitativo, teve como objetivo compreender os significados das relações amorosas, o ficar e o namoro na visão de dez participantes entre 17 a 23 anos de idade por meio de questionário. Os resultados revelaram que o ficar é permeado por beijos, carícias, e até mesmo pela relação sexual, em um breve período de tempo e, muitas vezes, com o intermédio de um amigo no momento da conquista. O compromisso do namoro, por sua vez, se estabelece quando o amor se faz presente na relação. Portanto, os adolescentes revelaram que optam pelo namorar, que pode ter início no ficar. Entretanto, para os participantes, a preferência dos jovens na atualidade é pelo ficar.
Love relationship: affective-sexual experiences of young people nowadays
Keywords: Adolescence; Love relationship; Contemporaneity; Adolescência; Relacionamento amoroso; Contemporaneidade